Inflammation, oxidative stress and genotoxicity responses to biodiesel emissions in cultured mammalian cells and animals. (27th May 2020) - Møller, Peter; Scholten, Rebecca Harnung; Roursgaard, Martin; Krais, Annette M.
Abstract: Biodiesel fuels are alternatives to petrodiesel, especially in the transport sector where they have lower carbon footprint. Notwithstanding the environmental benefit, biodiesel fuels may have other toxicological properties than petrodiesel. Particulate matter (PM) from petrodiesel causes cancer in the lung as a consequence of delivery of genotoxic polycyclic aromatic hydrocarbons, oxidative stress and inflammation. We have reviewed articles from 2002 to 2019 (50% of the articles since 2015) that have described toxicological effects in terms of genotoxicity, oxidative stress and inflammation of biodiesel exhaust exposure in humans, animals and cell cultures. The studies have assessed first generation biodiesel from different feedstock (e.g. rapeseed and soy), certain second generation fuels (e.g. waste oil), and hydrogenated vegetable oil. It is not possible to rank the potency of toxicological effects of specific biodiesel fuels. However, exposure to biodiesel exhaust causes oxidative stress, inflammation and genotoxicity in cell cultures. Three studies in animals have not indicated genotoxicity in lung tissue. The database on oxidative stress and inflammation in animal studies is larger (13 studies); ten studies have reported increased levels of oxidative stress biomarkers or inflammation, although the effects have been modest in most studies. The cell culture and animal studies have not consistently shown a different potency in effect between biodiesel and petrodiesel exhausts. Both increased and decreased potency have been reported, which might be due to differences in feedstock or combustion conditions. In conclusion, combustion products from biodiesel and petrodiesel fuel may evoke similar toxicological effects on genotoxicity, oxidative stress and inflammation.